Preliminary Results of the Exploration of the Fourth Section of the Upper Saltiv Burial Ground (USBG-IV) (1998–2021) - Aksionov, Victor; Skуrda, Valeriі (The Journal of V. N. Karazin Kharkiv National University. Series History, 2026)
The paper summarizes the preliminary results of the excavations undertaken on the fourth Upper Saltiv burial ground (USBG-IV) from 1998 to 2021 by the archaeological expeditions of M. F. Sumtsov Kharkiv Museum of History and V. N. Karazin Kharkiv National University. Over the years of the study of this section of the burial ground, 132 catacombs, ten burials in regular soil pits, five burials in pits with niches, seven dromoi without burial chambers, and one horse burial in a separate pit were discovered and investigated. These complexes yielded informative material that has enabled the researchers to propose a number of conclusions and hypotheses. In particular, the share of catacombs with a stone foundation at USBG-IV proved to be the largest among the catacomb necropolises of the region (30 percent). This likely indicates a higher property status of this group of the Alan population of Upper Saltiv. It was possible to identify ritual forms that had not been previously recorded at the Upper Saltiv burial ground, such as burials of animals (or people) in catacomb dromoi, which accompanied the main burials. Also for the first time on the site, catacombs were discovered with grooves intentionally made in the floor of the burial chambers. Another outcome of the study of USBG-IV is the identification of a new type of burial chambers — chambers with a two-level floor. It was established that the population of the Upper Saltiv settlement buried their dead at USBG-IV throughout the 9th century. Especially important are the catacomb burials, which represent the initial stage of the formation of the Saltiv culture in the upper reaches of the Siverskyi Donets. Thanks to the study of children’s burials in this section of the burial ground, it was established that the local population practiced the differentiation of children into three age groups. It was also possible to reconstruct the costume of an Alan woman belonging to the propertied elite of the Upper Saltiv community.